2019
DOI: 10.1001/jamaoncol.2019.0096
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 68Ga-PSMA-11 PET Accuracy in Localizing Recurrent Prostate Cancer

Abstract: In retrospective studies, 68 Ga-PSMA-11 positron emission tomographic (PET) imaging improves detection of biochemically recurrent prostate cancer compared with conventional imaging. OBJECTIVE To assess 68 Ga-PSMA-11 PET accuracy in a prospective multicenter trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

27
470
6
12

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 596 publications
(515 citation statements)
references
References 37 publications
27
470
6
12
Order By: Relevance
“…Eighteen studies reported the detection rate of 68 Ga‐PSMA PET in patients with a PSA 0.20–0.49 ng/mL . Combined, this involved 1078 patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies reported the detection rate of 68 Ga‐PSMA PET in patients with a PSA 0.20–0.49 ng/mL . Combined, this involved 1078 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Of these 567 patients, 367 (64.7%) had a positive 68 Ga‐PSMA PET. The detection rate ranged from 25% to 87.5% .…”
Section: Resultsmentioning
confidence: 99%
“…6 PSMA positron emission tomography (PET) imaging has demonstrated superiority to traditional imaging in the initial staging of intermediate-and high-risk disease 7 and in the detection of biochemical relapse in patients with low PSA values. 8,9 PSMA imaging using the radiotracer, 18 F-DCFPyL, also demonstrated improved sensitivity and specificity over conventional imaging modalities in the metastatic castration-resistant space. 10 Most metastatic prostate cancers spread through the blood as circulating tumor cells (CTCs), and enumeration of CTCs correlates with baseline and postbaseline prognosis in the mCRPC population.…”
Section: Introductionmentioning
confidence: 98%
“…PSMA‐targeted radioligand therapies, including 177 Lu‐PSMA‐617, successfully deliver β‐radiation directly to PCa cells . PSMA positron emission tomography (PET) imaging has demonstrated superiority to traditional imaging in the initial staging of intermediate‐ and high‐risk disease and in the detection of biochemical relapse in patients with low PSA values . PSMA imaging using the radiotracer,F‐DCFPyL, also demonstrated improved sensitivity and specificity over conventional imaging modalities in the metastatic castration‐resistant space …”
Section: Introductionmentioning
confidence: 99%
“…Prostate-specific membrane antigen (PSMA) is a cell surface transmembrane glycoprotein expressed on the cell surface by the majority of PCa cells, with its expression increasing in higher-grade malignancy [11,12]. Recently, PSMA-positron-emission tomography (PET)/CT imaging has become increasingly used in the detection of metastatic disease, especially in patients with biochemical recurrence after local treatment [13][14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%